Effect of warm-up and sodium bicarbonate ingestion on 4-km cycling time-trial performance - Gurton, W. H.; Faulkner, S. H.; James, R. M. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To examine whether an ecologically valid, intermittent, sprint-based warm-up strategy impacted the ergogenic capacity of individualized sodium bicarbonate (NaHCO3) ingestion on 4-km cycling time-trial (TT) performance.